Modeling the Socio-Economic Factors Affecting Islamic Insurance Adoption: A Structural Equation Modeling Analysis - Chetioui, Youssef; El Bouchikhi, Yassine; Lebdaoui, Hind; Ennassiri, Meryem; Jannah, Hanane; Yunsi, Ghita; Zhar, Imane; Ghamas, Ayoub (International Journal of Economics and Financial Issues, 2024)
While Islamic banking products have exhibited substantial growth in a number of Muslim countries, their market share remains restricted in others (i.e., Morocco). The current research aims to elucidate the key drivers of Islamic insurance (Takaful) adoption among Moroccan banking consumers. To achieve this goal, we propose and assess an integrated conceptual framework combining the Theory of Planned Behavior (TPB), the Diffusion of Innovation theory (DOI), and other constructs borrowed from prior literature (i.e., Religiosity). Through an online self-administered questionnaire, data was collected from 204 Moroccan respondents and analyzed using Partial Least Squares Structural Equation Modeling. Our findings reveal that while comparative advantage, religiosity and attitude positively influence respondents’ behavioral intention toward Takaful adoption, perceived complexity had a negative impact on takaful adoption. This research is among the first to evaluate the antecedents of behavioral intention towards Islamic insurance (Takaful) following its recent introduction to the Moroccan Market. Ultimately, it presents an important contribution to the limited literature on banking consumers’ perceptions of Islamic banking products in a market where Islamic banks are still at an infancy stage.